Comorbidity in People with Depression Seeking Help at Primary Health Care Centers in Santiago, Chile [Comorbilidad en Personas Con Depresión Que Consultan en Centros de la Atención Primaria de Salud en Santiago, Chile] - Martinez-Diaz, P (Sociedad Medica de Santiago, 2017)
Background: International evidence has shown the complex interaction between depression and chronic physical diseases. Depression in scenarios involving multiple comorbidities has not received enough attention in Chile. Aim: To characterize the depressed people who consult at Primary Health Care Centers (PHCCs), taking into account the presence of chronic physical or psychiatric comorbidity. Materials and Methods: A secondary analysis of databases used in a clinical trial. Two hundred fifty six adults seeking professional help were recruited in four PHCCs located in the Metropolitan Region. These people had a major depressive episode, identified with a structured psychiatric interview (MINI), and gave their informed consent to participate. Socio-demographic information was collected, depressive symptomatology was measured with the patient health questionnaire 9 (PHQ-9), psychiatric morbidity was assessed using the Mini International Neuropsychiatric Interview (MINI), and chronic physical diseases were self-reported by the patients. Descriptive analyses of all the variables were conducted. Results: Seventy percent of patients had a history of depression, with a median of two prior depressive episodes. Depressive symptoms were mostly considered as moderate to severe and severe and 31% of the patients had high suicide risk. Seventy eight percent displayed a physical or psychiatric comorbidity. Of these patients, 29% only had a chronic physical comorbidity, while 46% suffered from an additional psychiatric disorder. Conclusions: Depressed individuals who seek help at PHCCs constitute an especially complex population that must be treated taking into account multiple comorbidities. © 2017, Sociedad Medica de Santiago. All rights reserved.